Formulation and characterization studies of trimethyl chitosan / sodium alginate nanoparticles for targeted drug delivery. Issue 4 (4th April 2016) - Marci, Luisa; Meloni, Maria C.; Maccioni, Anna M.; Sinico, Chiara; Lai, Francesco; Cardia, Maria C.
Abstract: The objective of this study was to develop positively charged nanoparticles based on trimethyl chitosan and sodium alginate, as drug delivery systems able to interact with the sialic residues of the mucous membranes. Nanoparticles were prepared with the ionotropic gelation method, using sodium tripolyphosphate as cross‐linking agent. Ten different nanoparticle formulations were developed by varying the concentration of one component, while keeping constant the two others, or by varying the ratio between the three components. The aim of this formulation study was to determine the effect of both polymers and cross‐linker concentration and their ratios on nanoparticle dimensional parameters, such as mean size and size distribution, and surface charge. Overall results of the formulations study indicated that samples prepared with 2 mg/mL trimethyl chitosan concentration and different sodium alginate concentrations, namely 1 or 2 mg/mL, showed the best dimensional features, while the optimum concentration of cross‐linking agent was 1 mg/mL. Moreover, nanoparticle showed a positive charge surface, useful to interact with mucosal membranes. Abstract : A new positively charged drug delivery system, able to interact with mucous membranes, was developed for nose to brain application. Trimethyl chitosan was synthesized, mixed with sodium alginate to obtain polyelectrolyte complexes and then cross‐linked with sodium tripolyphosphate. Polymer ratios, as well as cross‐linking concentration, were selected as a function of dimensional parameters and surface charge.